Determinants of nurse satisfaction using insulin pen devices with safety needles: an exploratory factor analysis. Issue 1 (December 2015) - Veronesi, Giovanni; Poerio, Carmine; Braus, Alessandra; Destro, Maurizio; Gilberti, Lavinia; Meroni, Giovanni; Davis, Estella; Bossi, Antonio
Abstract Background A paucity of data exists to examine nurses' satisfaction with the use of insulin pens with safety needles in hospitalized patients with diabetes. We investigated major determinants of nurses' preference of the method of insulin administration in the context of a General Hospital in Northern Italy. Methods Consecutive patients admitted to three hospital units of different care intensity requiring insulin received insulin therapy through either the vial/syringe method (October to December 2012) or pen/safety needles with dual-ended protection method (January to March 2013). Before the implementation of insulin pens, floor nurses received a specific training program for proper insulin pen injection technique including individual testing of the devices (pen/safety needles). At the end of the study, nurses completed the Nursing Satisfaction Survey Questionnaire. Cronbach's alpha was used to determine the internal consistency and reliability of the questionnaire. Major determinants of satisfaction were investigated through an exploratory factor analysis. The association between each retained factor and time spent to teach patients how to self-inject insulin with pen devices was also investigated. Results Fifty-three out of 60 nurses (mean age ± SD 36.2 ± 8.5 years, 85 % women, 57 % with 10+ years of working experience) returned the questionnaire. Internal consistency of the questionnaire was satisfactory (Cronbach's alpha > 0.9). Three months after their introduction, about 92 % of nurses considered pen devices an "improvement" over the vial/syringe method. Two factors explained 85 % of nurses' satisfaction, one related to convenience and ease of use, and the other to satisfaction/time spent for dose preparation and administration. The latter factor was inversely correlated with time spent on patients' training tasks. Conclusions Nurses' satisfaction with pen devices was higher than previously reported, possibly reinforced by safety needles with dual-ended protection. Perceived workload was a major determinant of nurse satisfaction using pen devices with safety needles. To facilitate the introduction of insulin pens in the hospital setting, it should be specifically addressed during training programs in the switch-over period.